Deoxyamphimedine, a Pyridoacridine Alkaloid, Damages DNA via the Production of Reactive Oxygen Species - Chris M. Ireland; Louis R. Barrows; Cynthia D. Andjelic; Gisela P. Concepción; Deniz Tasdemir; Kathryn M. Marshall (Marine Drugs, 2009)
Marine pyridoacridines are a class of aromatic chemicals that share an 11H-pyrido[4,3,2-mn]acridine skeleton. Pyridoacridine alkaloids display diverse biological activities including cytotoxicity, fungicidal and bactericidal properties, production of reactive oxygen species (ROS) and topoisomerase inhibition. These activities are often dependent on slight modifications to the pyridoacridine skeleton. Here we demonstrate that while structurally similar to neoamphimedine and amphimedine, the biological activity of deoxyamphimedine differs greatly. Deoxyamphimedine damages DNA in vitro independent of topoisomerase enzymes through the generation of reactive oxygen species. Its activity was decreased in low oxygen, with the removal of a reducing agent and in the presence of anti-oxidants. Deoxyamphimedine also showed enhanced toxicity in cells sensitive to single or double strand DNA breaks, consistent with the in vitro activity.